Therapeutic effect of high-intensity focused ultrasound combined with transarterial chemoembolisation for hepatocellular carcinoma <5 cm: comparison with transarterial chemoembolisation monotherapy—preliminary observations - Kim, J (The British Institute of Radiology., 2012)
OBJECTIVE: To retrospectively compare the therapeutic effects of combined high-intensity focused ultrasound (HIFU) and transarterial chemoembolisation (TACE) with TACE alone for the treatment of non-advanced hepatocellular carcinomas (HCCs) <5 cm. METHODS: We retrospectively reviewed the tumour responses of 32 HCCs of 25 patients who underwent combined HIFU and TACE, and 46 HCCs of 32 patients who underwent TACE only. The mean follow-up observation of the TACE+HIFU group was on average 31 months and that of the TACE group was 33 months. Those patients who had undergone any other treatment modality (including systemic chemotherapy) during the follow-up observation period were excluded. The therapeutic effects were classified according to the modified Response Evaluation Criteria In Solid Tumors (mRECIST): complete response (CR), partial response (PR), stable disease (SD) and progressive disease (PD). Additionally, we defined CR', PR', SD' and PD' as the therapeutic effects “per tumour”. RESULTS: The disease control rate calculated using the RECIST criteria (CR+PR+SD/All) was 48% in the HIFU+TACE group and 47% in the TACE group (p=0.78, Fisher's exact test). The disease control rate “per tumour” (CR'+PR'+SD'/All) was 78% in the HIFU+TACE group and 54% in the TACE group (p=0.035, Fisher's exact test). In the HIFU+TACE group, no HIFU-related complications requiring treatment were observed. The median survival time was 57 months in TACE+HIFU group and 36 months in the TACE group (p=0.048). CONCLUSION: This preliminary study shows that the combination therapy of HIFU and TACE is more effective than TACE monotherapy for treating HCCs <5 cm.